IMPACT OF COVID-19 PANDEMIC ON BREAST CANCER SCREENING PROGRAM IN BASRA CITY (World Bulletin of Public Health, 2022)
Screening mammography offers the possibility of discovering malignant disease at an early stage, which is consequently treated early, thereby reducing the mortality rate; At the end of 2019, Wuhan city in China, became the centre of an outbreak of pneumonia of unknown cause, , known as severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) ,The World Health Organization (WHO) stated it as a global pandemic on March 11, 2020,in addition to the physical health effects of the virus in infected persons, the pandemic is also causing harmful social and mental health effects. Objective: The purpose of the study is to estimate the attendance rate of women to Early Detecting Clinics of Breast diseases in Basra City. Patients and Methods: across _sectional study was conducted from Feb.2020 to Jan.2021 .A total of 384 females where interviewed to assess the effect of COVID_19 on their attendance to Early Detecting Clinics of Breast diseases in Basra City .data analysed using spss version 26 software.
Keywords: Mammography; Screening; Pandemic; Vaccine